Efektivitas Program Keterampilan Vokasional Bagi Penyandang Tunagrahita di Sekolah Luar Biasa Negeri Binjai - Dinda Renita Sibagariang; Husni Thamrin (Concept: Journal of Social Humanities and Education, 2025)
People with intellectual disabilities are individuals with below-average intellectual abilities that impact their adaptive behavior and independence, in order to help develop their potential and skills. The Binjai State Special School organizes vocational skills programs, one of which is handicrafts, to equip students with economically valuable skills for their future. This study aims to determine the effectiveness of the handicraft vocational skills program for people with intellectual disabilities at Binjai State Special School using the effectiveness criteria according to Sutrisno (2007), namely program understanding, accuracy of target, timeliness, achievement of objectives, and tangible changes. The research employed a qualitative descriptive method with data collection techniques including observation, in-depth interviews, and documentation. The results of the study indicate that program understanding and targeting have been effective. However, in terms of timeliness, achievement of objectives, and tangible changes, the program has not been fully effective because students still require assistance in the product manufacturing process. Therefore, continuous support from the school, teachers, and families is needed so that this vocational skills program can run more optimally and sustainably.